2020
DOI: 10.1182/blood.2020005372
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome 20 loss is characteristic of breast implant–associated anaplastic large cell lymphoma

Abstract: Breast implant-associated anaplastic large cell lymphoma (BIA-ALCL) is a very rare type of T-cell lymphoma, uniquely caused by a single environmental stimulus. Here we present a comprehensive genetic analysis of a relatively large series of BIA-ALCL (n=29), for which genome-wide chromosomal copy number aberrations (CNA) and mutational profiles for a subset (n=7) were determined. For comparison, CNAs for ALK-negative nodal-ALCLs (n=24) were obtained. CNAs were detected in 94% of BIA-ALCLs with losses at chromos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 18 publications
1
25
0
Order By: Relevance
“…Cytogenetic studies performed in BIA-ALCL cell lines (TLBR-1, TLBR-2, and TLBR-3) have shown a complex karyotype and the absence of chromosomal abnormalities associated with other lymphomas, including systemic ALK- ALCL and pc-ALCL [ 179 ]. In addition to complex karyotypes, losses of chromosomes 1p, 10p, 20, and the gain of 19p have been observed in few cases [ 30 , 180 ]. The gain of 19p, the region where a JAK kinase is encoded, could help to clarify the pathogenesis of this entity, as this protein is involved in the phosphorylation of STAT1 and STAT3 [ 30 , 181 ].…”
Section: Breast Implant-associated Alclmentioning
confidence: 99%
“…Cytogenetic studies performed in BIA-ALCL cell lines (TLBR-1, TLBR-2, and TLBR-3) have shown a complex karyotype and the absence of chromosomal abnormalities associated with other lymphomas, including systemic ALK- ALCL and pc-ALCL [ 179 ]. In addition to complex karyotypes, losses of chromosomes 1p, 10p, 20, and the gain of 19p have been observed in few cases [ 30 , 180 ]. The gain of 19p, the region where a JAK kinase is encoded, could help to clarify the pathogenesis of this entity, as this protein is involved in the phosphorylation of STAT1 and STAT3 [ 30 , 181 ].…”
Section: Breast Implant-associated Alclmentioning
confidence: 99%
“…Complex karyotypes have been reported in several series with no translocations characteristic of lymphoma found [ 24 , 25 ]. Los-de Vries et al demonstrated characteristic loss of chromosome 20 in BIA-ALCL [ 11 ]. Shallow whole genome sequencing was performed on samples from twenty-nine patients and the most frequent copy number aberrancies (CNA) detected were gain of chromosome 2p (48%) and losses of 8p (48%), 20p (48%), and 20q (66%), which have been reported in other series [ 8 , 9 ].…”
Section: Genomic Characterisation Of Bia-alclmentioning
confidence: 99%
“…The loss of 20q appears to be specific to BIA-ALCL and rarely reported in other ALCLs or PTCL-NOS. Moreover, the copy number load was higher in seroma BIA-ALCL in comparison to tumour, which is suggestive of greater intertumoural heterogeneity and that progression to invasive disease is by subclone selection [ 11 ]. Whole genome copy number analysis by Blombery et al of thirteen patients revealed recurrent copy number loss of 1p21–22 (5/13) with a minimal deleted region containing the tumour suppressor gene RPL5 .…”
Section: Genomic Characterisation Of Bia-alclmentioning
confidence: 99%
“…3 More recently, amplification of chromosome 9p/PDL1 has become a potential marker for responses to immune J o u r n a l P r e -p r o o f checkpoint inhibition, [4][5][6] and loss of chromosome 18q was suggested as a marker for antiangiogenic treatment in metastatic colorectal cancer patients. 7 Other SCNAs offer diagnostic or prognostic value, including loss of chromosome 20q to diagnose breast implant-associated anaplastic large cell lymphoma, 8 or amplification of chromosome 2p/MYCN, which is associated with poor prognosis in neuroblastoma. 9 Genome-wide SCNA analysis is typically performed on DNA from tumor tissue biopsies using microarrays or shallow whole genome sequencing (sWGS).…”
Section: Introductionmentioning
confidence: 99%